Vidy sistematizatsii rossiiskogo zakonodatel'stva (Types of systematization of the Russian legislation) - I. Y. Gol’Tyapina (Russian Journal of Economics and Law)
Objective: to examine measures of administrative coercion applied to the media; to justify the need for changes to Articles 4 and 16 of the Law on mass media. Methods: the method of structural analysis, comparative-legal and formal legal methods. Results: The grounds for issuing warnings to mass media editorial offices are researched; the uneven category of abuse of freedom of mass information is reviewed; the legal nature of a written warning to the mass media editorial offices is analyzed; bases of the termination of the media are listed; impropriety of the terms of Articles 4 and 16 of the Law on mass media is revealed. Scientific novelty: The author analyzes the legal nature of a written warning to the mass media editorial offices on the fact of abuse of mass media freedom; it is proved that this measure is administrative-preclusive (however, it is not considered by officials as the measure of administrative punishment). It is revealed that for the second abuse of mass information freedom media shall be subject to termination in contradiction with the current version of Article 16. In contradiction with the generally accepted norms, a more severe measure is imposed, in particular, when the editorial office has met the requirements set out in the warning. Practical value: The study can contribute to streamlining the regulation of administrative coercive measures applicable to the mass media editorial offices, both judicial and extrajudicial. In addition, certain provisions may be useful in further scientific research.